The Role of Research in Undergraduate Studio Practice: A Qualitative Study Illustrating How Creative Research Aligns With Queer Theory and Indigenous Ways of Knowing - Ricci, Giana (Evidence Based Library and Information Practice, 2026)
Objective – This study investigated if and how research plays a role in the creative practice of undergraduate student artists.Methods – This was a qualitative study utilizing semi-structured interviews with 15 undergraduate students.Results – 60% of students firmly believed that research is part of their creative practice. 40% of students had mixed feelings about it. All students used books and the Internet in their creative practice at some point. Students preferred getting their books from bookstores rather than libraries. Students desired more support in finding resources generally.Conclusion – The study concluded that most students believe that research plays a role in their creative practice. It also concluded that students use print books and the Internet as their primary sources of inspiration and research for art making, and that the majority of students are not utilizing the library to access these resources. Analysis of the results also reveals similarities between creative research practices and queer theory, as well as between creative research practices and Indigenous ways of knowing.